THE IMPACT OF SOCIAL MEDIA ON PUBLIC HEALTH CAMPAIGNS: A STUDY OF MISINFORMATION AND VACCINE HESITANCY - Jamal Hamoud Ali Alrashdi, Abdulaziz Mohammed Yahya Moafa, Afaf Ibrahim Ali Showyee, Mutlaq Abdullah Mohammed Alsahli, Khalid Muanid Alanazi, Alaa Ibrahim Alsahaf, Muhamad Nafl Aldawsari, Abdulatef Ibrahim Alarfaj, Ammar Abdullah Alsahaf, ,; Hesham Mohammed Alhamad, Mohammed Adel Alnasser, Mohammed Ibrahim Mohammed Alghamdi, Abdulrahman Hamzah Alhasiri, Salem Mushari Saleh Aldughman, Naif Noman Alshammari, Emad Faisal Shabander, Dhari Dghaim Aldhfeeri, Mohsen Mohamed Al Qahtani, (Chelonian Research Foundation, 2022)
This research investigates how social media affects public health efforts, particularly in relation to disinformation and vaccination reluctance. Social media platforms have significantly transformed communication and information-sharing, offering both advantages and obstacles for public health campaigns. Social media, although potentially beneficial, has also become a fertile environment for spreading misinformation, especially about vaccinations. This tendency is concerning due to the worldwide initiatives to address vaccine-preventable illnesses and the recent COVID-19 pandemic. This research delves into the impact of social media on worsening vaccination hesitancy via an in- depth assessment and analysis of literature. The research examines how disinformation spreads on social media platforms and its effects on public health efforts. The research also investigates the impact of intentional misinformation operations conducted by other players, such foreign companies, on social media platforms. Social media platforms have facilitated the quick and extensive transmission of vaccination-related disinformation, leading to vaccine reluctance in certain groups. The research highlights the variables that contribute to social media being an effective platform for spreading disinformation, such as the lack of entrance barriers and the capability of fringe organizations to reach a broad audience. The statement emphasizes the impact of intentional misinformation tactics on shaping public opinions and actions around vaccinations. The research suggests several techniques to reduce the influence of social media on public health efforts. These actions involve improving regulations and policies to tackle the spread of misinformation, fostering cooperation between public health entities and social media platforms, creating customized strategies to target particular problems and knowledge deficiencies, increasing education and awareness regarding vaccines, and continuously researching and monitoring social media platforms. Keywords: Social media, public health campaigns, misinformation, vaccination reluctance, disinformation